2011
DOI: 10.1007/bf03326227
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals accumulation in plants growing in ex tin mining catchment

Abstract: ABSTRACT:The degree of contamination by heavy metals (arsenic, copper, lead, tin and zinc) in soil and transfer to plants has been studied. Specimens of plant species from five locations in an area of 10 x 10 m were sampled with their corresponding soils. Thirty six plant species including two shallow water aquatic plants were identified. Soil and plant specimens were analyzed by using inductively coupled plasma optical emission spectrometry. It was found that metal concentration in soil was highly variable wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(110 citation statements)
references
References 62 publications
6
82
2
6
Order By: Relevance
“…Quarry activity has the potential to destroying habitats and species Mabogunje [10]. Onyedika & Nwosu [11], Oluyemi et al [12] and Ashraf et al [13] suggested that quarrying activities are well known for their deleterious effect on the environment due to the deposition of large volume of waste on the soil. Ezeaku [14] then observed that exposure of the soil to run-off and the release of harmful minerals and chemicals through quarry activities contaminate soil, water, plant and air quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quarry activity has the potential to destroying habitats and species Mabogunje [10]. Onyedika & Nwosu [11], Oluyemi et al [12] and Ashraf et al [13] suggested that quarrying activities are well known for their deleterious effect on the environment due to the deposition of large volume of waste on the soil. Ezeaku [14] then observed that exposure of the soil to run-off and the release of harmful minerals and chemicals through quarry activities contaminate soil, water, plant and air quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Factor and Translocation Factor were analyzed by the equation (Madejon et al,2006;Ang et al,2010;Ashraf et al,2011;Madjid et al,2011;Maldonado-Magna, 2011) that were Bioaccumulation factor is , and translocation factor is…”
Section: Bioaccumulationmentioning
confidence: 99%
“…5. The capacity, performance and ability of vegetation to accumulate Pb for root, leaf and stem of mangrove vegetation's are determined as Bioaccumulation Factor of Pb (BAF) of Pb (Yoon et al, 2006;Ahmadpour, 2012;Buwono et al, 2005;Madejon et al,2006;Ang et al,2010;Ashraf et al,2011;Madjid et al,2011;Maldonado-Magna, 2011). BAF is determined by ratio between Pb accumulation of mangrove vegetation with sediment.…”
Section: Bioaccumulation Factor and Translocation Factor Of Pbmentioning
confidence: 99%
See 2 more Smart Citations